An online training-monitoring system to prevent nonfunctional overreaching - Piacentini, M. F.; Meeusen, R. (International Journal of Sports Physiology and Performance, 2015)
Purpose: This longitudinal case study evaluated the effectiveness of an online training-monitoring system to prevent nonfunctional overreaching (NFOR). Methods: A female master track and field athlete was followed by means of a daily online training diary (www.spartanova.com) and a weekly profile of mood state (POMS). The online diary consists of objective training data and subjective feelings reported on a 10-cm visual analog scale. Furthermore, parameters that quantify and summarize training and adaptation to training were calculated. The novelty consists in the inclusion of a specific measuring parameter tested to detect NFOR (OR score). Results: During track-season preparation, the athlete was facing some major personal changes, and extra training stress factors increased. Despite the fact that training load (TL) did not increase, the OR score showed a 222% and then a 997% increase compared with baseline. POMS showed a 167% increase in fatigue, a 38% decrease in vigor, a 32% increase in depression scores, and a total mood increase of 22%, with a 1-wk shift compared with the OR score. A 41% decrease in TL restored the OR score and POMS to baseline values within 10 d. Conclusion: The results demonstrate that immediate feedback obtained by "warning signals" to both athletes and coaches, based on individual baseline data, seems an optimal predictor of FOR/NFOR